Assessing geothermal/solar hybridization – Integrating a solar thermal topping cycle into a geothermal bottoming cycle with energy storage. (5th May 2020) - McTigue, Joshua D.; Wendt, Daniel; Kitz, Kevin; Gunderson, Joshua; Kincaid, Nick; Zhu, Guangdong
Highlights: A solar thermal topping cycle is proposed to hybridize a geothermal plant. The hybrid plant's thermal energy to electricity conversion efficiency is 32.9%. Anticipated cost reductions in thermal storage and solar fields reduce LCOE by 40%. The hybrid plant LCOE is 32% lower than a PV array with battery storage. Over-sizing the solar field and using storage improve flexibility and can reduce LCOE. Abstract: Geothermal and concentrating solar power (CSP) technologies typically use heat at different temperatures in their commercial deployments. This enables a technically viable hybridization of a solar topping cycle and a geothermal bottoming cycle at locations where both resources are available. In this article, an underperforming geothermal power system based at Burley, Idaho is used as a baseline to investigate the technical and economic potential of such a hybrid cycle. A direct thermal energy storage (TES) system is also integrated to overcome the intermittency of the solar resource. Design and off-design behavior of key components are modelled to simulate the annual performance of the hybrid system on an hourly basis. The sizing of the solar field and thermal storage is investigated and is seen to significantly impact the annual electricity generation and efficiency. Various cost scenarios for the solar field and thermal energy storage are investigated. An economic metric – levelized cost of electricity (LCOE) – is used to optimize the solar field sizing and TES capacity. The hybrid plant converts the additional solar heat input into additional work with an efficiency of 32.9%. Retrofitting a geothermal plant with solar and eight hours of energy storage can achieve an LCOE of 0.136 /kWhe in current cost scenarios and 0.081 /kWhe in a future cost reduction scenario. Although the hybrid system cannot directly compete with current PV systems without batteries, it has an LCOE 32% lower than that of a PV-battery system. This paper provides insights into the research and development of the future grid with a high renewable energy penetration and encourages further study of energy hybridization for improved efficiencies and economics.